Implementasi Asas Keterbukaan dan Partisipasi pada Seleksi Perangkat Desa dalam mewujudkan Good Governance Pemerintahan Desa - Ayu Wahyuni, Hesti; Anggraeniko, Litya Surisdani (LPPM Universitas Harapan Bangsa, 2024)
Good governance is the goal of every government organizer, including the village government. Important aspects in realizing good governance are transparency, accountability and participation as stipulated in Law No. 6/2014 on Villages. In line with this, Timbang Village, Kejobong Subdistrict, Purbalingga Regency has organized the selection of village officials to fill the position of Head of Hamlet II. The selection of village officials is an important part of organizing the village government which is also an implication of the principle of openness and community participation in its implementation. This research method is a juridical-empirical method using primary data on the implementation of the selection accompanied by literature review. Results and discussion, the implementation of the selection of village officials has accommodated community participation to be involved in the village government and is also an implication of the principle of openness to realize good governance through transparency of positions and selection results. The implementation of village apparatus selection is in line with the juridical provisions of Purbalingga Regent Regulation No. 27/2018 on Guidelines for Filling Village Apparatus in Purbalingga Regency. Keywords: good governance, openness, participation, village apparatus